Light chain deposition disease as monoclonal gammopathy of renal significance-a rare disease with scarce therapy; a case report - Fereshteh Saddadi; Bahareh Marghoob; Mohamadhasan Fallahkohan (Journal of Nephropathology)
The kidneys are one of the main organs which involved in light chain deposition disease (LCDD). The usual renal presentations are renal failure with or without nephrotic range proteinuria and microscopic hematuria. There is not a standard therapy of kidney involvement in this disease which named as monoclonal gammopathy of renal significance (MGRS). The present case is focused on a new therapeutic strategy.